Bangsa Cina; Antara Profetis Dan Diabolistik - Ilham Darajat (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2019)
Comprehensive understanding of prophetic text which is correlated with anthropological phenomena is difficult to achieve. This occurs because there are a number of reading subjectivity and scientific traditions that have been hegemonized by the domination of authoritative communities and their interests. Likewise, what happened to the phenomenon of humiliation (the Chinese nation and its civilization), instead of obtaining a source of prophetic text that placed the nation on an egalitarian anthropological degree with other nations, it received sharp attention because of its strong correlation with the text